Acid Tolerant and Acidophilic Microalgae: An Underexplored World of Biotechnological Opportunities - Abiusi, Fabian; Trompetter, Egbert; Pollio, Antonino; Wijffels, Rene H.; Janssen, Marcel (Frontiers in Microbiology, 2022)
Despite their large number and diversity, microalgae from only four genera are currently cultivated at large-scale. Three of those share common characteristics: they are cultivated mainly autotrophically and are extremophiles or tolerate “extreme conditions.” Extreme growth conditions aid in preventing contamination and predation of microalgae, therefore facilitating outdoor cultivation. In search for new extremophilic algae suitable for large-scale production, we investigated six microalgal strains able to grow at pH below 3 and belonging to four genera; Stichococcus bacillaris ACUF158, Chlamydomonas acidophila SAG 2045, and Chlamydomonas pitschmannii ACUF238, Viridiella fridericiana ACUF035 and Galdieria sulphuraria ACUF064 and ACUF074. All strains were cultivated autotrophically at light intensity of 100 and 300 μmol m−2 s−1 and pH between 1.9 and 2.9. The autotrophic biomass productivities were compared with one of the most productive microalgae, Chlorella sorokiniana SAG 211-8K, grown at pH 6.8. The acid tolerant strains have their autotrophic biomass productivities reported for the first time. Mixotrophic and heterotrophic properties were investigated when possible. Five of the tested strains displayed autotrophic biomass productivities 10–39% lower than Chlorella sorokiniana but comparable with other commercially relevant neutrophilic microalgae, indicating the potential of these microalgae for autotrophic biomass production under acidic growth conditions. Two acid tolerant species, S. bacillaris and C. acidophila were able to grow mixotrophically with glucose. Chlamydomonas acidophila and the two Galdieria strains were also cultivated heterotrophically with glucose at various temperatures. Chlamydomonas acidophila failed to grow at 37°C, while G. sulphuraria ACUF64 showed a temperature optimum of 37°C and G. sulphuraria ACUF74 of 42°C. For each strain, the biomass yield on glucose decreased when cultivated above their optimal temperature. The possible biotechnological applications of our findings will be addressed.